Menstrual Blood Banking: A concept âbest out of wasteâ in the area of stem cell research - Ancy Mathew, Frincy Francis, Sheeba Elizabeth Joel, (Journal of Medical Biomedical and Applied Sciences, 2016)
The primitive cells also known as the stem cells are miraculous cells that can regenerate into various organs such as the heart, bones, muscles and nervous system. The emergence of stem cell technology and the successful impact of the stem cells research has brought ray of hope to the diseased population of the world. Remarkable responses have been created in the medical specialties by stem cell therapies with the most popularized concept of cord blood which has helped in many major diseases like Thalassemia, Alzheimerâs disease. Likewise stromal cells of menstrual origin or Menses-Menstrual Blood âDerived Stem Cells have demonstrated cells to be equally multi potent like the umbilical cord blood and the dental pulp stem cells except for the myth among the public that the menstrual blood is a bad blood that needs to be discarded. Menstrual stem cells could offer a lot of advantages over the other stem cells as the source is easy to find because every woman is a source, quantity available is more, the fear of tissue rejection is minimal and above all the question of ethical issues related to using embryonic stem cells are avoided. Researchers across the globe have come to a conclusion that the cells derived from menstrual blood may represent a potentially unlimited, easily available and cost effective source used in regenerative therapies. The electronic databases using which was done were Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Online (Medline), Pub med, EBSCO, Embase, and Science Direct. The search terms include Menstruation, Menstrual Blood, and Menstrual Blood Stem Cells. Menstrual Blood Banking, Endometrial Stem Cells. Menstrual Regenerative Cells. Menstrual Blood Banking appears to be an innovative, promising, cost effective, novel and ethically acceptable alternative concept which needs to be popularized in the field of medicine.